RELEVANCE OF THE CONCEPT OF FAIR PRICES AND PROFITS FOR THE COMMUNITY, (STUDY OF IBN TAYMIYYAH THOUGHTS ON JUSTICE IN TRADE) - Zaenuddin Mansyur (Universitas Islam Negeri Mataram, 2019)
The urgency of justice in determining a price or profit in trade at least can construct the concerns of the leading cleric's Ibn Taymiyyah to bring up the theories associated with it. Ibn Taymiyah's involvement in bringing up the theory of justice in the field of trade was nothing but to improve the economic conditions of the community where he lived. Ibn Taimiyah's concern in the economy when he gave rise to fair price theory. According to him that a fair price is a price that can be formed by market forces that run freely is not determined by the party who has the goods so that the shortage of goods (supply decreases) or increasing population (demand rises) is not a reason to raise prices as freely as possible. While the theory of determining a fair price for Ibn Taymiyyah had an impact on determining a fair profit as well. Where profit-taking may also not be determined by the owner of the goods but profit-taking is based on market conditions in ways that are generally accepted. This means that the profit to be taken is a normal profit that can be received by all parties by providing the same price to the general public event even though there is a great need for the merchandise. Thus, determining a price is very relevant to making a profit. Where profits can be determined through market prices that do not cause gaps and exploitation to buyers.